The spiritual doorway in the brain : a neurologist's search for the God experience - Nelson, Kevin (Dutton, 2011)
The world's leading neurologist on out-of-body and near-death experiences shows that spirituality is as much a part of our basic biological makeup as our sex drive or survival instinct. In his cutting-edge research, Nelson has discovered that spiritual experiences take place in one of the most primitive areas of the brain. In this eloquent, reverent book, he relates the moving stories of patients and research subjects, brain scan analysis, evolutionary biology, and examples of transcendence from literature to reveal the machinery in our heads that enables us to perceive miracles--whether you are an atheist, Buddhist, or the most devout Catholic. Ultimately he makes clear that spiritual experiences are not the exception in human life, but rather an inescapable and precious part of every one of us.--From publisher description.